A tanya és a zárt település kapcsolata – társadalomföldrajzi megközelítésben - Duró, Annamária (Tér és Társadalom, 1990)
The specific feature of the Hungarian scattered farmstead (tanya) is derived from its peculiar relationship with the core settlement, the so called parent town. The 1949 local administration reform modified this very relationship: as a result of the formation of designated scatteredfarmstead-centres into central villages, new core settlements were established on the territory of scattered farmstead areas in rural-market-town regions. But the hoped rapid liquidation °I tanyas was not happening: villages with scattered farmsteads remained „divided settlements", though with their inner areas increasing–both in population number and extent–to the detriment of outer areas. Taking this modified relationship as a starting point, the author seelcs the connecting links between present scattered farmsteads and their central village, the former parent town, or neighbouring settlements. In a social geographical approach, these links are identified as spatial relationships developed by tanya inhabitants while exercising basic social functions. Thanks to a research grant, the author could study tanyas in the outer areas of two villages in a sandy region–from a social geographical point of view. The paper summarizes the major results of this field study, highlighting four elements out of the system of basic social functions: the spatial links of housing, production, consumption and social life.